Historiography of the Central American Military Confrontations, 1808 to 1824 - Arguedas Zamora, Aarón (2022)
This article reviews the historiography on military confrontations in Central American between 1820 and 1824.  In the foreground, it looked over those writings that described it in a general way. In a second, the narrative published in each province. Additionally, to study this period should be done in two phases and must include new actors in the development of independence. Consequently, this paper suggests that the military conflicts of independence and the armed forces of Central America are part of a process that must be examined as such.